2012
DOI: 10.11113/jt.v40.395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porosity on Mechanical Properties of Metal Matrix Composite: An Overview

Abstract: Keliangan di dalam tuangan komposit matriks logam (KML) adalah satu kecacatan yang boleh mempengaruhi kekuatan bahan terutamanya di dalam KML bertetulang partikel. Merujuk kepada kajian lepas, faktor-faktor pembentukan keliangan adalah berpunca daripada gelembung-gelembung udara yang memasuki leburan matriks logam, wap air yang terdapat pada permukaan partikel, gas yang terperangkap semasa proses pencampuran, evolusi hidrogen dan pengecutan tuangan semasa pemejalan. Namun, kebanyakkan kajian menunjukkan punca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 16 publications
4
37
0
3
Order By: Relevance
“…The low material removal rate is observed at high stirring speed and low stirring speed; these results are supported by the result of Aqida et al [15] an investigation in which it is concluded that at high speed porosity of MMC were increased drastically after a certain limit of stirring speed, also at low speed clustering and non-homogenous micrographs are observed.…”
Section: Characteristic Graphssupporting
confidence: 72%
“…The low material removal rate is observed at high stirring speed and low stirring speed; these results are supported by the result of Aqida et al [15] an investigation in which it is concluded that at high speed porosity of MMC were increased drastically after a certain limit of stirring speed, also at low speed clustering and non-homogenous micrographs are observed.…”
Section: Characteristic Graphssupporting
confidence: 72%
“…From equation (13), the values of k and m are obtained from the plot of ln(H v ) versus ln( [20]. Therefore, increasing the porosity results in decreased mechanical properties; however, the majority of applications involving porous ceramics require excellent mechanical properties [35][36][37]. The increase of the hardness with the further increase in the Sm doping above x=0.02 may be attributed to the substitution of Zn 2+ ions by Sm 3+ ions in the crystal lattice which decrease the weak lattice stresses on the surface by removing the defect centers [38].…”
Section: Vickers Microhardness Measurementsmentioning
confidence: 99%
“…Multiple mechanisms contribute to porosity in SLM parts. These include shrinkage, gas entrapment during solidification [21,22], and adhesion of partially molten particles to surfaces between layers [23]. Additionally, depending on the wettability, capillary forces and surface tension of the melt pool, a defect known as "balling" can occur which results in uneven subsequent powder layers and, consequently, pores upon processing of the material [24].…”
Section: Introductionmentioning
confidence: 98%